The evolution of Microsoft Windows operating systems after 2001 - Wójtowicz, Bartłomiej; Wójcik, Norbert (Journal of Computer Sciences Institute, 2024)
The purpose of this article is to present the most important changes that occurred with the release of successive versions of Windows after 2001 and to compare Windows XP, Windows 7, Windows 10, Windows 11 in terms of performance, resource consumption, speed of file operations and usability of the graphical user interface. For this purpose, research scenarios were prepared to enable for reliable testing, two computer workstations were prepared to install the operating systems under study, and research experiments were conducted. The results of the research were presented graphically and analyzed. Conclusions were drawn to answer the question of whether the usability of Windows operating systems increased with the advent of new versions of the system.